2022
DOI: 10.3389/fendo.2022.1005553
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum Klotho levels and the prevalence of diabetes among adults in the United States

Abstract: BackgroundDiabetes is a critical contributor to the pathogenesis of cardiovascular diseases. Klotho is an anti−aging protein with cardiovascular-renal protective effects. However, the relationship between serum Klotho levels and diabetes remains poorly understood.ObjectivesThis study aimed to investigate the relationship between serum Klotho levels and diabetes in US adults.MethodsWe analyzed the cross-sectional data obtained from 13751 subjects aged 40-79 years in the National Health and Nutrition Examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…However, only a few clinical studies have shown associations between FGF23, α-klotho and various indexes related to T2DM, including insulin resistance (measured by homeostasis model assessment of insulin resistance), dyslipidemia, resistin levels, and obesity status, suggesting that an imbalance in the FGF23/α-klotho axis may result in an unfavorable lipid profile, which could contribute to the development or progression of both T2DM and atherosclerosis [ 31 33 ]. Although several studies have shown a negative correlation between α-klotho and diabetes [ 34 , 35 ], recent published studies have ruled out this association [ 28 , 36 ]. The present study demonstrated positive correlations between serum FGF23 levels and FGF23/α-klotho ratio with T2DM and a negative correlation between serum α-klotho levels and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few clinical studies have shown associations between FGF23, α-klotho and various indexes related to T2DM, including insulin resistance (measured by homeostasis model assessment of insulin resistance), dyslipidemia, resistin levels, and obesity status, suggesting that an imbalance in the FGF23/α-klotho axis may result in an unfavorable lipid profile, which could contribute to the development or progression of both T2DM and atherosclerosis [ 31 33 ]. Although several studies have shown a negative correlation between α-klotho and diabetes [ 34 , 35 ], recent published studies have ruled out this association [ 28 , 36 ]. The present study demonstrated positive correlations between serum FGF23 levels and FGF23/α-klotho ratio with T2DM and a negative correlation between serum α-klotho levels and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In mobile examination centers (MECs), blood samples of participants with obtained consent were collected in the morning after fasting for at least 9 h [ 16 ]. The samples were packaged on dry ice and then stored at -80 °C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10] It also contributes to the regulation of glucose metabolism and holds promise as a new therapeutic target for diabetes. [11,12] Although numerous studies suggest a close relationship between Klotho and the progression of T2DM and insulin sensitivity impairment, [13][14][15] the connection between Klotho and insulin resistance remains incompletely elucidated. Therefore, the objective was to explore the link between serum Klotho levels and insulin resistance, utilizing data from the National Health and Nutrition Examination Survey (NHANES) covering the years 2007 to 2016.…”
Section: Introductionmentioning
confidence: 99%